2019
DOI: 10.5435/jaaos-d-17-00727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NSAIDs on Bone Healing Rates: A Meta-analysis

Abstract: Introduction: NSAIDs inhibit osteogenesis and may result in delayed union or nonunion. The purpose of this meta-analysis was to determine whether their use leads to delayed union or nonunion. Methods: We systematically reviewed the literature reporting the effect of NSAIDs on bone healing. We included studies of pediatric and adult patients NSAID exposure and healing bone. The outcomes of interest were delayed union, nonunion, or pseudarthrosis with at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 42 publications
0
105
1
2
Order By: Relevance
“…Though the literature is not conclusive, a recently published meta-analysis reported increased odds of nonunion (odds ratio = 2.07, 95% CI, 1.19 to 3.61) in orthopedic patients taking high doses or long courses of NSAIDs following fracture osteotomy and fusion surgeries. 82 In this study, low doses of NSAIDs (less than 125 mg/day diclofenac, 150 mg/day indomethacin, or 120 mg/day ketorolac) taken for less than 2 weeks were not shown to increase the odds of nonunion. 82 Several other studies also suggest that short courses of NSAIDs do not affect nonunion rates.…”
Section: Patients Should Be Discharged With a Prescriptionmentioning
confidence: 55%
“…Though the literature is not conclusive, a recently published meta-analysis reported increased odds of nonunion (odds ratio = 2.07, 95% CI, 1.19 to 3.61) in orthopedic patients taking high doses or long courses of NSAIDs following fracture osteotomy and fusion surgeries. 82 In this study, low doses of NSAIDs (less than 125 mg/day diclofenac, 150 mg/day indomethacin, or 120 mg/day ketorolac) taken for less than 2 weeks were not shown to increase the odds of nonunion. 82 Several other studies also suggest that short courses of NSAIDs do not affect nonunion rates.…”
Section: Patients Should Be Discharged With a Prescriptionmentioning
confidence: 55%
“…Dodwell et al reported an increased risk of nonunion among NSAID‐treated patients in the pooled effect of 11 studies (OR 3.0 [95% CI 1.6, 5.6]), but no effect was observed when only 7 high‐quality studies were included . Another meta‐analysis by Wheatley et al also showed that NSAID use was associated with an increased risk of nonunion or delayed union (OR 2.07 [95% CI 1.19, 3.61]), but similar to the temporal effect observed in the animal studies, no association was found in studies with a short duration of NSAID treatment . In addition, no association was observed in studies with low‐dose NSAIDs or in pediatric groups .…”
Section: Introductionmentioning
confidence: 80%
“…Another meta‐analysis by Wheatley et al also showed that NSAID use was associated with an increased risk of nonunion or delayed union (OR 2.07 [95% CI 1.19, 3.61]), but similar to the temporal effect observed in the animal studies, no association was found in studies with a short duration of NSAID treatment . In addition, no association was observed in studies with low‐dose NSAIDs or in pediatric groups . Neither of these two meta‐analyses examined the difference between the effects of COX‐2 selective NSAIDs and nonselective NSAIDs.…”
Section: Introductionmentioning
confidence: 97%
“…A recent meta-analysis15 concluded NSAIDs generally have a negative effect on bone healing secondary to impairing osteogenesis. The effect may be dose or time dependent because low-dose/short duration exposure did not affect union rates.…”
Section: Indicationsmentioning
confidence: 99%